Multiple excitatory actions of orexins upon thalamo-cortical neurons in dorsal lateral geniculate nucleus - implications for vision modulation by arousal - Lukasz Chrobok (Nature Portfolio, 2017)
Abstract The orexinergic system of the lateral hypothalamus plays a crucial role in maintaining wakefulness and mediating arousal in a circadian time-dependent manner. Due to the extensive connections of orexinergic neurons, both orexins (OXA and OXB) exert mainly excitatory effects upon remote brain areas, including the thalamus. The dorsal lateral geniculate nucleus (DLG) is a relay thalamic centre for the visual system. Its thalamo-cortical (TC) neurons convey photic information from the retina to the primary visual cortex. The present study shows that orexins are powerful modulators of neuronal activity in the DLG. OXA directly depolarised the majority of neurons tested, acting predominately on postsynaptic OX2 receptors. Moreover, OXA was found to increase excitability and enhance neuronal responses to both glutamate and γ-aminobutyric acid (GABA). Mechanistic studies showed the involvement of voltage-gated calcium currents and GIRK channels in the observed depolarisations. Immunohistochemical staining showed sparse orexinergic innervation of the DLG during the light phase, with increased density at night. We hypothesise that the depolarising effects of orexins upon DLG neurons may facilitate signal transmission through the visual thalamo-cortical pathway during behavioural arousal. Thus, the action of orexin on DLG TC neurons may underlie the circadian/behavioural modulation of vision.